IoT-Based English Translation Teaching from the Perspective of Artificial Intelligence - Dandan Liu (International Journal of Antennas and Propagation)
In recent years, with the development of artificial intelligence, the Internet of Things (IoT) has become a research hotspot in industry and academia. At the same time, as a derivative tool of artificial intelligence, machine translation based on the IoT is constantly being applied to English translation and its teaching. In teaching, helping students learn English translation has been the focus of machine translation in recent years. Compared with human translation, machine translation is more efficient and convenient. However, machine translation also has some problems. Compared with traditional human translation, it cannot meet the requirements of faithfulness, expressiveness, and elegance of translation. In many fields, neural network translation is comparable to human translation. In the field of English translation teaching, neural network translation has broad prospects. With the gradual maturity of neural network translation, we should think about how to use neural network translation to make it a powerful English translation teaching tool instead of sticking to traditional teaching and cultivating students who are completely unable to compare it with neural network translation. Therefore, in the context of rapid AI iteration, college English translation teaching should also keep pace with the times. With the help of tools such as neural network translation, English translation talents who can skillfully use AI technology can be trained quickly and efficiently so that they can keep pace with the times and master the power of AI. The research in this paper provides important guidance for the application of artificial intelligence and the Internet of Things, especially for intelligent relaying.